A study of Privatisation of Public Enterprises and it's implications on Economic Policy and Development - Monika, Mrs. (Innovative Research Thoughts, 2018)
Academics, economists, and politicians were more likely to support public ownership of industries in the 1960s and 1970s than they were to support private ownership. However, by the late 1980s, public policy had shifted from favoring state control over the production and distribution of goods and services to encouraging private investment and management. The ineffective provision of services, loss-making state-owned enterprises (SOEs), excessive public debt, and low rates of economic development that included "state failure" as defined by the World Bank contributed to this. As a result, privatization has gained popularity in many nations as a means to promote efficiency, incentivize investment, and release public resources for use in infrastructure and social programs that boost economic development and distributional equality. Nonetheless, privatization has been criticized in recent years. Privatization has been criticized for a number of reasons, the most prominent being the misuse of market power and the resulting losses in social welfare. Most people in developing nations believe that the wealthiest profit more from privatization than the poor. To that end, the purpose of this research was to undertake an empirical examination of the claims and counterclaims about the effect of privatization on economic development and wealth distribution in developing nations. Eighty developing nations that privatized their SOEs between 1991 and 2002 make up the research sample. The study's results suggest that privatization did not significantly affect GDP growth but did have varying results for income distribution. However, the research shows that strong governance and other country-specific factors may be more significant than economic policy per se in fostering development and decreasing income disparity.